KENYÜ A CUSTOMARY LAW OF ANGAMI TRIBE: REFLECTIONS ON CULTURAL IDENTITY AND PRACTICE IN CONTEMPORARY ANGAMI SOCIETY - Assumi, K Hinoca; Singh, Nongmaithem Kishorchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article discusses Kenyü of Angami customary law as an institution that influences cultural identity, social behaviour and community mobilisation in the town of Kohima, Nagaland, India. Field work material with a mixed-method design based on semi structured interviews, with 40 under-graduate Angami students in Kohima district are utilized as primary sources while literature from folklore, anthropology and legal studies are referred to explore the flexibility of customary law as a regulatory and cultural institution. The study reveals that Kenyü as reflected in prohibitions and taboos still functions as a moral edifice and an institution of legitimacy in which decision-making is arrived at through commnunity consensus. Although Angami customary law faces hindrance from generational changes, Christianity, globalization, and encounters with state law as guaranteed by Article 371A of the Indian Constitution, it has developed beyond those obstructions by adapting and creating a new culture. Folklore and oral traditions take on paramount importance in passing these values from one generation to another, ensuring the continuity of culture while permitting reevaluation by younger generations in new circumstances. The study has shown that Angami customary law, and its basis on Kenyu, continues to serve as an effective vehicle for participation and conflict resolution in the communities, as a result, remains relevant in the socio-political fabric of Nagaland.